2013
DOI: 10.1093/eurheartj/eht251
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies 6p21 as novel risk locus for dilated cardiomyopathy

Abstract: The present study reveals a novel genetic susceptibility locus that clearly underlines the role of genetically driven, inflammatory processes in the pathogenesis of idiopathic DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 34 publications
5
97
0
2
Order By: Relevance
“…Autoimmune diseases in humans fulfil at least two of the major criteria proposed by Witebsky and Rose 79 80. In keeping with the findings in other conditions, in myocarditis and in autoimmune DCM there may be familial aggregation48–50 and HLA associations 51 81. Other main clinical autoimmune features (box 2) include the findings of mononuclear cell infiltrates, abnormal expression of HLA class II and/or adhesion molecules on cardiac endothelium in the absence of viral genomes (assessed by PCR on EMB) in affected patients and family members,52 53 increased levels of serum cytokines and cardiac autoantibodies (aabs) in patients and family members,7 23 54 55 57–64 67 68 70 72 74–78 and response to immunosuppression or immunomodulation 26–29 53 56 73…”
Section: Pathogenesissupporting
confidence: 53%
“…Autoimmune diseases in humans fulfil at least two of the major criteria proposed by Witebsky and Rose 79 80. In keeping with the findings in other conditions, in myocarditis and in autoimmune DCM there may be familial aggregation48–50 and HLA associations 51 81. Other main clinical autoimmune features (box 2) include the findings of mononuclear cell infiltrates, abnormal expression of HLA class II and/or adhesion molecules on cardiac endothelium in the absence of viral genomes (assessed by PCR on EMB) in affected patients and family members,52 53 increased levels of serum cytokines and cardiac autoantibodies (aabs) in patients and family members,7 23 54 55 57–64 67 68 70 72 74–78 and response to immunosuppression or immunomodulation 26–29 53 56 73…”
Section: Pathogenesissupporting
confidence: 53%
“…[6][7][8]12,15 With the exception of MIAT, all analyzed lncRNAs were differentially expressed in patients with MI: antisense hypoxia inducible factor 1α, KCNQ1OT and MALAT1 were upregulated, whereas ANRIL was downregulated. MALAT1 and antisense hypoxia inducible factor 1α are known to be induced under hypoxia.…”
Section: Circulation Research September 12 2014mentioning
confidence: 99%
“…In another study, the presence of variants in Toll-like receptors which play a key role in the innate immune response were associated with poorer cardiac function in 158 patients 99. Finally, Meder et al 100 present data associating the locus containing major histocompatibility genes (MHC I and II) with DCM. The authors identified multiple single nucleotide polymorphisms on chromosome 6p21.…”
Section: Dilated Cardiomyopathymentioning
confidence: 92%